Effect of transcranial direct current stimulation for patients with disorders of consciousness: A systematic review and meta-analysis - Ma, Hui; Zhao, Kehong; Jia, Chengsen; You, Jiuhong; Zhou, Mei; Wang, Tingting; Huang, Cheng (Frontiers in Neuroscience, 2023)
Introduction Transcranial direct current stimulation (tDCS) could potentially facilitate consciousness improvement in patients with disorders of consciousness (DOC). The aim of this study was to investigate the therapeutic efficacy of tDCS on consciousness recovery for patients with DOC. Methods Eight databases were systematically searched from their inception to June 2022. Quality of included studies were assessed using PEDro score and Cochrane’s risk of bias assessment. All statistical analyses were performed using RevMan software. Seventeen studies with 618 patients were identified eligible for this study, and fifteen studies with sufficient data were pooled in the meta-analysis. Results The results of meta-analysis showed a significant effect on increasing GCS scores (MD = 1.73; 95% CI, 1.28–2.18; P < 0.01) and CRS-R scores (MD = 1.28; 95% CI = 0.56–2.00; P < 0.01) in favor of the real stimulation group as compared to sham. The results of subgroup analysis demonstrated that only more than 20 sessions of stimulation could significantly enhance the improvement of GCS scores and the CRS-R scores. Moreover, the effect of tDCS on CRS-R score improvement was predominant in patients with minimal conscious state (MCS) (MD = 1.84; 95% CI = 0.74–2.93; P < 0.01). Conclusion Anodal tDCS with sufficient stimulation doses appears to be an effective approach for patients with MCS, in terms of CRS-R scores. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022336958.